Analysis and exploitation of harmonics in wireless power transfer (H-WPT): passive UHF RFID case. Issue 2 (September 2014) - Andia Vera, Gianfranco; Duroc, Yvan; Tedjini, Smail
<x content-type="archive" xml:space="preserve">Abstract</x> This paper discusses novel methodologies for the characterization of harmonic signals generated by wireless powered devices, i.e. passive ultra-high frequency (UHF) radio frequency identification (RFID) tags, due to the wireless power transferred from reader to tag. Theoretical aspects, as well as measurements to characterize these non-linear phenomena are exposed. Particular care is taken to explain the analysis methodology and setup for two kinds of characterization measurements: radiated and conducted. The existence of harmonic signals carrying information is exploited in an advanced application example. A dual-band RFID tag is designed to increase the backscattered harmonic level in the tag-to-reader link. Measurement of this dual band tag demonstrates the exploitation of the hitherto neglected harmonic power; it also opens the door to more advanced applications exploiting the harmonic-link communication.